Mathematical Modelling of Hydromagnetic Convection from a Rotating Sphere with Impulsive Motion and Buoyancy Effects - Anwar Bég, O.; Takhar, H. S.; Nath, G.; Chamkha, A. J. (Nonlinear Analysis: Modelling and Control, 2006)
The convective heat transfer on a rotating sphere in the presence of magnetic field, buoyancy forces and impulsive motion is examined theoretically and numerically in this paper. We apply a boundary layer model comprising the balance equations for x and y direction translational momentum and heat transfer, and solve these coupled non-linear partial differential equations using Blottner’s finite-difference method [1]. The numerical solutions are benchmarked with the earlier study by Lee [2] on laminar boundary layer flow over rotating bodies in forced flow and found to be in excellent agreement. The effects of magnetic field, buoyancy parameter, Prandtl number and thermal conductivity parameter on translational velocities and temperature and other variables (shear stress etc) are presented graphically and discussed at length. The problem finds applications in chemical engineering technologies, aerodynamics and planetary astrophysics.
Keywords: hydromagnetic; convection; rotation; Prandtl number; chemical engineering devices; industrial aerodynamics; impulsive motion; numerical; finite difference; Blottner method